"Three-Year Reproducibility of Natural Head Position; A Longitudinal Study " - M. Nouri; M. Mir; A. Akbarzadeh; A. Marami (Tehran University of Medical Sciences, 2006)
Statement of problem: Few longitudinal studies have evaluated the reproducibility of natural head position (NHP) with more than six months follow-up. Purpose: The present investigation was conducted to estimate the reproducibility of NHP in adult cases after three years. Materials and Methods: This descriptive study was performed on 27 volunteer dental students, 19-29 years of age. One radiograph and two photographs were taken in a NHP. The time interval between the two photographs was 4 to 10 minutes (short-term period) and a radiograph was taken approximately 2 years, 6 months after the first photograph. These were obtained by one operator and device in standing subjects. In order to evaluate NHP reproducibility, the photographs and radiographs were superimposed on the true vertical line and the angle between the true horizontal (from N') and N'-Pog' was assessed. The mean, standard deviation (SD) and confidence interval of the three angles along with short- and long-term method errors were calculated. Correlation coefficient of the angles was analyzed according to time. The differences of registration in genders were determined by t-test. Results: Short-term reproducibility between the two photographs was 2.44º and the long term reproducibility between the first photograph-radiograph and the second photograph-radiograph was 3.23º and 3.38º, respectively. Method error in registration of NHP by photography and radiography showed no systematic bias. Gender had no significant effect on reproducibility. Conclusion: NHP is a reproducible position in adults after 3 years. This position is more consistent in men. Photographic and radiographic registrations of NHP indicate similar results.